Discussion of “employee stock options, EPS dilution, and stock repurchases” - Larcker, David F. (Journal of Accounting and Economics, 2003)
Bens, Nagar, Skinner, and Wong conclude that stock repurchase decisions are related to the impact of stock options on the ability of firms to meet historical EPS growth targets. Although this is a provocative conclusion, this interpretation is questionable because managers are assumed to be extremely myopic, the results are highly sensitive to the choice of EPS growth target, firms with a high P/E ratio produce results that are completely inconsistent with the research hypothesis, and alternative explanations that are unrelated to earnings management are not considered.